P‐120: High‐Mobility IGZO Thin‐Film Transistors Fabricated on a Flexible PET Monofilament Fiber for Wearing Display. Issue 1 (25th September 2020) - Kim, Chan Young; Park, Jun Hong; Park, Sang-Hee Ko; Choi, Kyung Cheol
Abstract : In this study, InGaZnO (IGZO) thin‐film transistors (TFTs) were fabricated on a flexible polyethylene terephthalate (PET) monofilament fiber. Although the TFTs were fabricated on a cylindrical substrate, we were able to implement flexible fiber TFTs with a high mobility of 7.8 cm 2 /Vs by optimizing the process temperature and patterning method.